Treatment of chronic periodontitis with the use of osteoplastic materials (LLC "Endo Press", 2020)
Restoration of bone lesions in the area of periapical destruction in patients with chronic periodontitis remains a pressing problem of modern dentistry. Under the supervision of the authors 296 teeth of 230 patients were treated. Endodontic treatment for all patients was conducted in full accordance with generally accepted standards. In the study group patients before the filling of channels in the area of periapical bone destruction be output osteoplastic material (freeze-dried autobone and β-tricalcium phosphate), which resulted in improved outcomes for observations in the period up to 3 years.